Commentary: The Moment of Truth – transcending Knowledge through Myriads of Creativity - Matrahah, Izaddin (Idealogy Journal; Vol 4 No 2 (2019): Idealogy Journal (September 2019), 2019)
Letter to Editor - No Abstract